Meningococcal Carriage in ‘Men Having Sex With Men’ With Pharyngeal Gonorrhoea - Morselli, Sara; Gaspari, Valeria; Cantiani, Alessia; Salvo, Melissa; Foschi, Claudio; Lazzarotto, Tiziana; Marangoni, Antonella (Frontiers in Cellular and Infection Microbiology, 2022)
We assessed the characteristics of Neisseria meningitidis pharyngeal carriage in a cohort of ‘men having sex with men’, including patients with pharyngeal Neisseria gonorrhoeae infection. In the period 2017-2019, among all the oropharyngeal samples tested for gonorrhoea from MSM attending a STI Clinic in Bologna (Italy), we randomly selected 244 N. gonorrhoeae-positive samples and 403 negatives (n=647). Pharyngeal specimens were tested for N. meningitidis presence, by the detection of sodC gene. N. meningitidis-positive samples were further grouped by PCR tests for the major invasive genogroups (i.e., A, B, C, W, and Y). A molecular assay, targeting capsule transporter gene, was used to determine meningococcal capsular status. Overall, 75.8% (491/647) of samples tested positive for sodC gene, indicating a pharyngeal meningococcal carriage. Meningococcal colonisation was significantly more frequent in younger subjects (P=0.009), with no association with HIV infection. Non-groupable meningococci represented most of pharyngeal carriages (about 71%). The commonest N. meningitidis serogroup was B (23.6%), followed by C (2.1%), Y (1.8%) and W (1.1%). Meningococci were often characterized by the genetic potential of capsule production. Interestingly, a negative association between N. meningitidis and N. gonorrhoeae was found: pharyngeal gonorrhoea was significantly more present in patients without meningococcal carriage (P=0.03). Although preliminary, our data added knowledge on the epidemiology of meningococcal carriage in MSM communities at high risk of gonococcal infections, gaining new insights into the interactions/dynamics between N. meningitidis and N. gonorrhoeae.